Supply chain quality integration: relational antecedents and operational consequences. Issue 3 (12th June 2018) - Yu, Yubing; Huo, Baofeng
Abstract : Purpose: This paper aims to examine the impacts of relational capital on supply chain quality integration (SCQI) and operational performance from the holistic perspective of the entire supply chain. Design/methodology/approach: Structural equation modeling with LISREL was used to test the conceptual model based on data collected from 308 companies in China. Findings: The results indicate that with the exception of internal relational capital not having a significant impact on customer quality integration, supplier, internal and customer relational capital have positive impacts on supplier, internal and customer quality integration, which consequently improve operational performance. The results also show that internal relational capital has positive impacts on supplier and customer relational capital, and internal quality integration has positive impacts on supplier and customer quality integration. Practical implications: The results provide important managerial insights for the improvement of operational performance through the development of relational capital and the implementation of SCQI practices throughout the supply chain. Originality/value: The authors contribute to the relational capital and supply chain quality management literature by exploring the effectiveness of relational capital in improving SCQI and operational performance from the holistic perspective of the entire supply chain. The findings enrich the knowledge of SCQI management from the perspective of relational capital.